Brandeis and America - Dawson, Nelson L. (University Press of Kentucky, 1989)
Louis D. Brandeis is a figure of perennial significance in American history. Brilliant lawyer, innovative reformer, seminal thinker, and judicial giant, he left few significant issues in American society untouched during the course of his long and productive career. The last several decades have been particularly rich in Brandeis historiography, creating the need for a work surveying current scholarship and addressing critical issues. Brandeis and America more than meets this need. Six distinguished Brandeis scholars -- David J. Danelski, Nelson L. Dawson, Allon Gal, David W. Levy, Philippa St.